MENTAL STATE OF A PERSON AFTER THE SUDDEN DEATH OF A RELATIVE AND FEATURES OF A DOCTOR-PSYCHOLOGISTS ASSISTANCE FOR THIS GROUP OF PATIENTS - D. Assonov (Bogomolets National Medical University, 2016)
In the article it is analyzed the data of the scientific literature of recent years, concerning the mental state of a person after the sudden death of a relative. It has been hypothesized that the mental condition is influenced by different factors, each of them makes it only the inherent features of the state. These factors are causes and conditions of death, socioeconomic status of the family, the status and role in the family of the deceased, age, etc. The information that is present in the scientific literature, although confirms the hypothesis, as there are enough studies that suggest that the mental state is different in all cases of sudden death and strongly dependent on the influence of different factors, but is rather patchy and incomplete. Also, perhaps through lack of theoretical knowledge, methods of work of the doctor-psychologist with the patients with the sudden loss of a relative are badly developed. Therefore, in this article there is an attempt to systematize the information about the influence of factors on the mental state, to classify them and to develop based on this information recommendations relating to the provision of doctor-psychologist assistance to this group of patients. Particularly, it was overwieved the typical person's mental state after the sudden death of a relative - the grief, and the most common psychopathological reactions, which is manifestations of maladjustment to death - post-traumatic stress disorder, mafor depressive disorder, prolonged grief. Further work was concentrated especially on the mental state and psychopathological reactions that occur under the influence of a factor. As a result, after the analysis of the literature, there were developed the recommendations about the work in different cases of a sudden death: with the widowers and widows of suddenly died, with children who suddenly lost their parents, with people whose relatives died due to suicide, homicide, military operations, accidents, there were proposed the most effective tactics of therapy that take into account the peculiarities of the influence of various factors on the mental state.